Task-irrelevant emotional expressions are not mimicked, but may modulate the mimicry of task-relevant emotional expressions - Mauersberger, Heidi; Blaison, Christophe; Hess, Ursula (Frontiers in Psychology, 2025)
Emotional mimicry—the imitation of others’ emotions—is an empathic response that helps to navigate social interactions. Mimicry is absent when participants’ task does not involve engaging with the expressers’ emotions. This may be because task-irrelevant faces (i.e., faces that participants were instructed to ignore) are not processed. To assess whether processed task-irrelevant faces are also not mimicked, we conducted three studies [Study 1: N = 74 participants (27 men; Mage = 26.9 years); Study 2: N = 53 participants (20 men; Mage = 25.8 years); Study 3: N = 51 participants (7 men; Mage = 26.8 years)] using an affective priming paradigm in which one face was task-relevant and one was to be ignored, as a framework to explore the impact of disregarded yet still perceptually processed faces on mimicry. We found that even though both faces were processed, only task-relevant faces were mimicked. Hence, our studies suggest that emotional mimicry depends not only on emotional processing as such but also on the way participants prioritize one piece of information over another. Further, task-irrelevant faces interfered with the mimicry of task-relevant faces. This suggests that even though incongruent task-irrelevant faces do not elicit an empathic (mimicry) response, they still may provide a context that can change the meaning of task-relevant faces and thus impact on the mimicry response.